Circulating inflammatory markers impact cognitive functions in bipolar depression. (August 2021) - Poletti, Sara; Mazza, Mario Gennaio; Calesella, Federico; Vai, Benedetta; Lorenzi, Cristina; Manfredi, Elena; Colombo, Cristina; Zanardi, Raffaella; Benedetti, Francesco
Abstract: Background: Cognitive impairment is a core feature of bipolar disorder, with a prevalence of about 64.4% during episodes and 57.1% in euthymia. Recent evidences suggest that cognitive deficits in BD may follow immune dysfunction and elevated levels of inflammatory cytokines have been reported during periods of depression, mania and euthymia, suggesting the presence of a chronic, low-grade inflammatory state. The aim of the study is to investigate if immune/inflammatory markers and especially chemokines associate to cognitive performances. Methods: Seventy-six consecutively admitted inpatients with a depressive episode in course of bipolar disorder performed a neuropsychological evaluation with the Brief Assessment of Cognition in Schizophrenia and plasma blood levels of cytokines, chemokines and growth factors were analyzed with Luminex technology. Results: Higher levels of IL-1β, IL-6, CCL2, CCL4, CCL5, CXCL10, and bFGF are associated with the likelihood of having a poor cognitive performance. Limitations: Limitation include the lack of a group of healthy controls and the lack of information regarding previous psychopharmacological treatments, alcohol and tobacco use. Conclusions: Our results confirm the importance of chemokines in bipolar disorder and suggest that inflammatory markers suggestive of a low-grade inflammatory state could contribute to the neurocognitive deficits observed in depressed patients. Highlights: Circulating inflammatory markers associate with cognitive functions. Higher levels of CXCL10, CCL2, CCL4, CCL5, bFGF associate with poor cognitive performances. Chemokines are involved in cognitive deficits in bipolar disorder.